2012
DOI: 10.1371/journal.pone.0051994
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic Acid Supplementation Does Not Improve Western Diet-Induced Cardiomyopathy in Rats

Abstract: Obesity increases risk for cardiomyopathy in the absence of hypertension, diabetes or ischemia. The fatty acid milieu, modulated by diet, may modify myocardial structure and function, lending partial explanation for the array of cardiomyopathic phenotypy. We sought to identify gross, cellular and ultrastructural myocardial changes associated with Western diet intake, and subsequent modification with docosahexaenoic acid (DHA) supplementation. Wistar and Sprague-Dawley (SD) rats received 1 of 3 diets: control (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 77 publications
0
14
0
Order By: Relevance
“…Previously reported gas chromatography data confirm that dietary DHA was incorporated into the phospholipid fraction of myocardial septal tissue (CON 13.79 ± 0.49 area %, WES 10.82 ± 0.43 area %, WES+DHA 31.64 ± 0.50 area %; p<0.0001). [3]…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously reported gas chromatography data confirm that dietary DHA was incorporated into the phospholipid fraction of myocardial septal tissue (CON 13.79 ± 0.49 area %, WES 10.82 ± 0.43 area %, WES+DHA 31.64 ± 0.50 area %; p<0.0001). [3]…”
Section: Resultsmentioning
confidence: 99%
“…[3] We previously reported that WES and WES+DHA feeding were associated with similarly increased LV cranial wall thickness and decreased LV internal diameter during diastole, compared to CON animals. [3] The present model is useful in that fat-fed rats do not develop increased body weight or visceral adiposity, hypertriglyceridemia or systemic insulin resistance,[3] allowing for examination of diet effects in the absence of these modulators of myocardial structure and function. The absence of conventional comorbidities is probably due to similar energy intake and feed efficiency across groups, attributed to the large amount of dietary fat in both high-fat diets and resultant reduced intake by weight.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations